Jòrgi Reboul, un parcours singulier vers l’occitanisme à travers l’histoire du XXe siècle - François Courtray (Lengas)
Jòrgi Reboul is one of the great poets of twentieth century Marseille. Known for his innovative literary work which upset the codes of Occitan poetry in the early 1930s, he was also and above all a man of action, engaged in the defence of the Oc language and culture. A member of the Félibrige that he has viewed rather critically from the outset, he founded in 1925 Lou Calen de Marsiho which shone for nearly 60 years over the Phocaean city. He became involved in politics with the Parti Prouvençau for the elections of 1936, promoted teaching Provencal at school, founded and ran a youth hostel, assisted both in strengthening ties with the Catalans and in supporting them during the Spanish war. After World War II, he broke with the Félibrige to rally the Occitan wave and the IEO whilst continuing his actions in favour of teaching the Oc language, Catalans and the great fights of the 1960s- 1970. Under his leadership, the Calen soon became the cradle of the current CREO Provence.